EPID-11. SYSTEMATIC REVIEW ON TREATMENT-RELATED HAEMATOLOGICAL ADVERSE EVENTS AFTER TEMOZOLOMIDE FOR A CNS TUMOUR. Issue 2 (22nd June 2018) - Bos, Daniel; Gijtenbeek, Anja; Muller, Annemarie; Meeteren, Antoinette Schouten-van
Abstract: BACKGROUND: Temozolomide is a widely used alkylating cytostatic drug for CNS tumours. Severe treatment-related haematological adverse events (tHAE) after the application of temozolomide are reported whilst the true incidence is elusive. The aim of this study is to determine the incidence, the risk-factors for, and course of secondary haematological adverse events after treatment with temozolomide in patients with CNS tumours. METHODS: We reviewed the English literature between 1995-2016 on cases describing treatment-related haematological adverse events after temozolomide and set up a country-wide survey among (paediatric) neuro-oncologists in the Netherlands. RESULTS: In 20 out of 199 manuscripts deriving from the literature search 26 cases (age 0-69, median 40, 5 years) were found with a severe tHAE event after temozolomide: 5 aplastic anemia, 5 acute lymphoblastic leukemia, 9 acute myeloblastic leukemia, 1 diffuse large B-cell lymphoma, 6 myelodysplastic syndrome and 1 mixed lineage leukemia. Karyotype was detected in 17/26 cases, mainly monosomy 5&7. Quality check of the literature mainly showed missing data on predisposing family history. Seven additional cases of a t-HAE after TMZ in CNS a tumour were discovered via a clinical survey in the Netherlands. The median latency in developing a t-HAE was 14 months, the survival after t-HAE was median 4, 5 months. CONCLUSIONS: tHAE is rare and develops relatively early after treatment with temozolomide, while insufficient insight could be found for risk-factors for a t-HAE after temozolomide. Although most patients die from their secondary tHAE, its course differs substantially between individual cases.